Evaluation of FMS scores of competitive CrossFit athletes by gender - Yol, Y. (International Journal of Disabilities Sports and Health Sciences, 2023)
Functional Movement Screening System (FMS) is a testing and assessment protocol used to evaluate the body movement and movement capacity of athletes or physically active individuals. Analysis of FMS scores by gender can provide important information to personalize training programs, identify weak points, and improve the movement quality of athletes. Therefore, the aim of this study was to evaluate the FMS scores of competitive CrossFit athletes according to gender. A total of 22 athletes, 14 males with a mean age of 26.79±5.16 years and 8 females with a mean age of 32.38±3.74 years participated in the study. Participants were administered the FMS™ test consisting of seven tasks (per the FMS™ manual). In the analysis of the data, after the normality distribution was made, the Man-Whitney U test was performed for the data that did not show the normal distribution in an independent two-group comparison. A statistically significant difference was found in the right(p=0.04) and left (p=0.04) shoulder mobility score, shoulder mobility final score (p=0.01), and active straight leg raise score-right (p=0.02) measurements of the athletes according to gender. As a result, females were found to have higher 'shoulder mobility' and 'active straight leg raising' scores than males on a movement basis. In addition, the total FMS scores were found to be above average for both genders.